(untitled) (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This study aimed to investigate studentsâ€™ lived experience of Quillbot utilization in academic writing. The qualitative phenomenology method was used in this study to dig deeper into studentsâ€™ lived experiences that they interpreted while using Quillbot. The result based on the data analysis showed some lived experiences that the students interpreted such as Quillbotâ€™s benefits and studentsâ€™ future use of Quillbot, studentsâ€™ perceptions of autonomy and assistance, studentsâ€™ ethical consideration when utilizing Quillbot, and studentsâ€™ adoption of Quillbotâ€™s suggestion. The results of this study also emphasized students’ awareness that Quillbot is a supporting tool that cannot replace their writing skills. This study provides valuable insight into how students interact with Quillbot, how it influences their writing process, and broadens the perspective of teachers, lecturers, instructors, and the wider community who often consider AI to have negative impacts on studentsâ€™ learning process.